Navigating Rhizo-Curriculum in EFL Classrooms: A Narrative Approach to Teachers’ Experiences - Kairienė, Aida; Mažeikienė, Natalija (Pedagogika, 2025)
This study aims to explore and disclose the experiences of secondary school teachers navigating the rhizo-curriculum in English foreign language classrooms. Narrative inquiry has been applied to achieve this aim. The results revealed that implementation of the rhizo-curriculum depends on the teacher’s personality; teachers partly implement the rhizo-curriculum into the teaching and learning process because they usually follow the strict curriculum and prepare learners them for exams.